Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Tô Văn Tám - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Tô Văn Tám (Số: 11714/BCT-KH) ngày 06/12/2016